Digitale Arbeitswelten im Mittelstand : Veränderungen und Herausforderungen /: Veränderungen und Herausforderungen. (2019) - Becker, Wolfgang; Ulrich, Patrick; Fibitz, Alexandra; Schuhknecht, Felix; Reitelshöfer, Eva
No abstract available